Multispacecraft observations of fundamental poloidal waves without ground magnetic signatures. Issue 7 (24th July 2013) - Takahashi, Kazue; Hartinger, Michael D.; Angelopoulos, Vassilis; Glassmeier, Karl‐Heinz; Singer, Howard J.
Abstract: [1] Poloidal standing Alfvén waves observed by spacecraft usually have a second harmonic standing wave structure. On very rare occasions, fundamental poloidal waves have been observed in association with giant pulsations observed on the ground. In this paper, we report multisatellite observations of fundamental poloidal waves that did not produce any clearly associated magnetic pulsations on the ground. The waves were observed on 10 November 2008, at 1830 Universal Time (UT) at THEMIS‐A and THEMIS‐D and at 2010 UT at THEMIS‐E as these spacecraft passed L 11 and magnetic local time (MLT) 0900. The GOES‐11 geostationary satellite ( L 7) also observed poloidal waves at 1730 UT when it was at 0900 MLT. The poloidal waves at THEMIS were characterized by narrow‐band oscillations (frequency 4 mHz) of the ion bulk velocity and magnetic field in the radial direction. We identify the waves at THEMIS to be the fundamental mode on the basis of the wave properties observed slightly south of the magnetic equator: large velocity amplitude, small magnetic field amplitude, and 90° phase delay of the magnetic field relative to the velocity. The azimuthal wave number is found to be 70 (if we assume westward propagation) or 200 (if we assume eastward propagation) from the phase delay between THEMIS‐A and THEMIS‐D. This wave number explains why there were no corresponding magnetic field oscillations on the ground. These observations imply that only a subset of fundamental poloidal waves excited in the magnetosphere is observed on the ground as giant pulsations. Key Points: Poloidal waves were observed by THEMIS and GOES. The waves were high‐m fundamental standing Alfven waves. The waves did not propagate to the ground.